Watch where they hide [large type] - Hall, Tamron; Taylor, T. Shawn (Hall, Tamron. Jordan Manning novel, 2024)
Journalist Jordan Manning delves into the case of a mother in danger and uncovers a dangerous web of secrets that could lead right to the missing woman--or put Jordan in the crosshairs of her abductors.